Myosteatosis Significantly Predicts Persistent Dyspnea and Mobility Problems in COVID-19 Survivors - De Lorenzo, Rebecca; Palmisano, Anna; Esposito, Antonio; Gnasso, Chiara; Nicoletti, Valeria; Leone, Riccardo; Vignale, Davide; Falbo, Elisabetta; Ferrante, Marica; Cilla, Marta; Magnaghi, Cristiano; Martinenghi, Sabina; et al. (Frontiers in Nutrition, 2022)
Background: persistent symptoms including dyspnea and functional impairment are common in COVID-19 survivors. Poor muscle quality (myosteatosis) associates with poor short-term outcomes in COVID-19 patients. The aim of this observational study was to assess the relationship between myosteatosis diagnosed during acute COVID-19 and patient-reported outcomes at 6 months after discharge. Methods: myosteatosis was diagnosed based on CT-derived skeletal muscle radiation attenuation (SM-RA) measured during hospitalization in 97 COVID-19 survivors who had available anthropometric and clinical data upon admission and at the 6-month follow-up after discharge. Dyspnea in daily activities was assessed using the modified Medical Research Council (mMRC) scale for dyspnea. Health-related quality of life was measured using the European quality of life questionnaire three-level version (EQ-5D-3L). Results: characteristics of patients with (lowest sex- and age-specific tertile of SM-RA) or without myosteatosis during acute COVID-19 were similar. At 6 months, patients with myosteatosis had greater rates of obesity (48.4% vs. 27.7%, p=0.046), abdominal obesity (80.0% vs. 47.6%, p=0.003), dyspnea (32.3% vs. 12.5%, p=0.021) and mobility problems (32.3% vs. 12.5%, p=0.004). Myosteatosis diagnosed during acute COVID-19 was the only significant predictor of persistent dyspnea (OR 3.19 [95% C.I. 1.04; 9.87], p=0.043) and mobility problems (OR 3.70 [95% C.I. 1.25; 10.95], p=0.018) at 6 months at logistic regression adjusted for sex, age and BMI. Conclusion: Myosteatosis diagnosed during acute COVID-19 significantly predicts persistent dyspnea and mobility problems at 6 months after hospital discharge independent of age, sex and body mass. ClinicalTrials.gov (NCT04318366)